CYBERLIBERTARIANISM IN THE MID-1990S - Pace, Jonathan (AoIR Selected Papers of Internet Research, 2020)
This paper analyzes libertarian internet discourse in the mid-1990s, focusing on the events surrounding the passage of the Communications Decency Act of 1996, which criminalized obscene and indecent content on the internet. During this episode, hackers, early adopters, computer professionals, technology lobbyists, and civil society advocates embraced a libertarian way of thinking about the internet and the state — a way of thinking I refer to as cyberlibertarianism. These groups had long-standing libertarian dispositions, although their anti-statism ranged from a left-libertarianism, concerned with concentrations of power in the state and in the market, to a civil-libertarianism, concerned with the integrity of constitutional protections, to a right-libertarianism, concerned with laissez-faire market conditions. In responding to the events of the decade, and following from their established dispositions, these groups converged on a libertarian narrative about the internet and the state. According this narrative, the state was overbearing, intrusive, compromised, and uninformed — and therefore a threat to the internet as a sphere of freedom, individualism, competition, and innovation. This libertarian narrative structured their arguments against specific acts of state intervention. In the case of the Communications Decency Act, they argued that the regulatory measure undermined the promise of the internet as a venue of free speech, an object of the free market, and a conduit for the free flow of information.